2017
DOI: 10.4236/psych.2017.84038
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Brief Self-Compassion Intervention Program on Self-Compassion, Positive and Negative Affect and Life Satisfaction

Abstract: Self-compassion (Neff, 2003b) is a newly developed construct of positive psychology while a plethora of studies has highlighted its beneficial outcomes on people's psychological prosperity. This study aimed to explore the effectiveness of a brief self-compassion training program on self-compassion, life satisfaction and positive and negative affect as well as to contribute new knowledge by investigating whether changes in self-compassion can significantly predict changes in positive affect. A sample of 42 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 38 publications
2
27
1
1
Order By: Relevance
“…Global self-compassion scores are attained by reverse coding the negative items, and then averaging across the mean scores of each facet. The scale has been found to have good levels of internal consistency when using a 5-point Likert scale (α = .92; Mantelou and Karakasidou 2017;Neff 2003b), and good test-retest reliability (α = .93 ;Neff 2003b;Neff et al 2005;Neff and Pommier 2013). In this study, the measure was also highly reliable (α = .94 and ω = .74).…”
Section: Adhd Traitsmentioning
confidence: 50%
“…Global self-compassion scores are attained by reverse coding the negative items, and then averaging across the mean scores of each facet. The scale has been found to have good levels of internal consistency when using a 5-point Likert scale (α = .92; Mantelou and Karakasidou 2017;Neff 2003b), and good test-retest reliability (α = .93 ;Neff 2003b;Neff et al 2005;Neff and Pommier 2013). In this study, the measure was also highly reliable (α = .94 and ω = .74).…”
Section: Adhd Traitsmentioning
confidence: 50%
“…One possible way to prevent and mitigate rumination and promote positive thoughts by targeting emotion is selfcompassion [101][102][103][104]. Self-compassion can be thought of as treating oneself with care and concern especially during times of failure, mistakes, feelings of inadequacy, and painful experiences [105].…”
Section: Example: Diet and Fitness Appsmentioning
confidence: 99%
“…A meta-analysis of 20 studies reported large (as defined [10]) associations between selfcompassion and various types of mental distress including depression and anxiety [11]. Further, intervention studies found that enhancing self-compassion also improved various outcomes including mental health [12], well-being [13], and life satisfaction (14). These studies reported that practicing compassion towards one's inadequacies and life challenges can counter shame and self-criticism, which otherwise might lead to poor mental health and well-being [15].…”
Section: Introductionmentioning
confidence: 99%